Mechanism of Enhanced Dermal Permeation of 4-Cyanophenol and Methyl Paraben from Saturated Aqueous Solutions Containing Both Solutes - Romonchuk, W.J.; Bunge, A.L. (Skin pharmacology and physiology, 2010)
Dermal permeation through human epidermis and uptake into isolated human stratum corneum (SC) that was and was not delipidized were measured for 2 model compounds, 4-cyanophenol (CP) and methyl paraben (MP), from saturated aqueous solutions containing 1 or both compounds. Because the solutions were in equilibrium with the pure CP and MP, the thermodynamic activity of the compounds was constant. Compared with compounds that are known permeation enhancers, MP and CP would not normally be expected to act as enhancers. Nevertheless, when both compounds were present, the steady-state fluxes through the epidermis increased by factors of 5.2 and 2.6 for MP and CP, respectively. Within the variability of the measurements, this increase in MP flux is consistent with the 6.4-fold increase in the SC uptake, which occurs primarily into the nonlipid regions of the SC. In contrast, the 1.6-fold increase in CP uptake when MP is present is too small to explain the increase in CP flux. These results suggest that CP enhances the skin permeation of MP by primarily increasing the solubility of MP in the SC, especially in the nonlipid regions, while MP increases the skin permeation of CP by enhancing both the solubility and diffusivity of CP in the SC.